Effects of Caragana korshinskii tannin on fermentation, methane emission, community of methanogens, and metabolome of rumen in sheep - Niu, Xiaoyu; Xing, Yuanyaun; Wang, Jingyao; Bai, Lili; Xie, Yongfang; Zhu, Shouqian; Sun, Mei; Yang, Jing; Li, Dabiao; Liu, Yuanyuan (Frontiers in Microbiology, 2024)
The purpose of this research was to investigate impact of dietary supplementation of Caragana korshinskii tannin (CKT) on rumen fermentation, methane emission, methanogen community and metabolome in rumen of sheep. A total of fifteen crossbred sheep of the Dumont breed with similar body conditions, were divided into three groups (n = 5), which were fed with CKT addition at 0, 2% and 4%/kg DM. The study spanned a total of 74 days, with a 14-day period dedicated to adaptation and a subsequent 60-day period for conducting treatments. The results indicated that the levels of ammonia nitrogen (NH3-N) and acetate were reduced (P < 0.05) in rumen sheep fed with 2% and 4% CKT; The crude protein (CP) digestibility of sheep in 2% and 4% CKT groups was decreased(P < 0.05); while the neutral detergent fiber (NDF) digestibility was increased (P < 0.05) in 4% CKT group. Furthermore, the supplementation of CKT resulted in a decrease (P < 0.05) in daily CH4 emissions from sheep by reducing the richness and diversity of ruminal methanogens community, meanwhile decreasing (P < 0.05) concentrations of tyramine that contribute to methane synthesis and increasing (P < 0.05) concentrations of N-methy-L-glutamic acid that do not contribute to CH4 synthesis. However, CH4 production of DMI, OMI, NDFI and metabolic weight did not differ significantly across the various treatments. To sum up, the addition of 4% CKT appeared to be a viable approach for reducing CH4 emissions from sheep without no negative effects. These findings suggest that CKT hold promise in mitigating methane emissions of ruminant. Further investigation is required to evaluate it effectiveness in practical feeding strategies for livestock.